Clinical and Histopathologic Characteristics of Metastatic and Locally Advanced Cutaneous Basal Cell Carcinomas. (December 2021) - Baker, Laura X.; Grilletta, Erica; Zwerner, Jeffrey P.; Boyd, Alan S.; Wheless, Lee
Abstract : Abstract: Locally advanced or metastatic basal cell carcinomas (laBCCs or mBCCs) are rare, with few case series providing information on their epidemiology. We aimed to describe the clinical and histologic features of locally advanced and metastatic basal cell carcinomas. Forty cases of laBCC or mBCC were identified by searching Vanderbilt's database from 1984 to January 2019. A retrospective chart review was performed. Pathology slides were available for 23 cases (13 mBCCs and 10 laBCCs). Twenty-one of 23 cases were Clark level IV or V, with a mean depth of invasion of >7 mm for both types. The mean mitotic rate was 4.4 mitoses/mm 2 for laBCCs and 3.3 mitoses/mm 2 for mBCCs. Ulceration was identified in 7 laBCC and 8 mBCC cases. Perineural invasion was present in 2 laBCC and 6 mBCC cases, with 3 mBCCs invading nerves >0.1 mm. Of 13 mBCC cases, histologic subtypes included infiltrative (n = 9), nodular (n = 7), morpheaform (n = 4), and superficial (n = 2), with multiple patterns present in some specimens. 10 of 13 patients with mBCC had local recurrence before metastasis. In summary, we identified several potential markers of high-risk BCC, including perineural invasion, deep invasion, elevated mitotic rate, and local recurrence of the primary tumor.